(untitled) (Journal of the College of Basic Education, 2023)
The Arab Islamic civilization is one of the greatest civilizations that appeared to human existence.Which had the high honor in advancing the movement of scientific, cognitive and human development and the rest of the fields ofThis life is for the best. The intellectual and scientific side had a clear and significant impact.Far and near, the Arabs are the first to write books of biographies, biographies and genealogies.lead in this field.If we follow what the Arab Muslims achieved in this field, this preface would not have absorbed it.However, we register with pride and honor for the Arabs who used to take care of their lineages as they cherished them, and this is something that was lacking.Other peoples who do not have a glorious past like the past of our great ancestors. When Islam cameHe tried to reduce tribal fanaticism and that allegiance is to Islam, but he stressed the necessity of lineage and Arabism.. This is what appeared to us clearly in the works through which Arab Muslim scholars dealt with the recording ofThe Prophet’s biography, through which it was necessary for them to translate those who supported the Holy Prophet (may God’s prayers and peace be upon him)Peace be upon him and his family (and his victory was from the Companions, may God be pleased with them all), and that is why the books of translations appeared.And due to the presence of the honorable prophetic hadiths in the biographies, the need required to take care of the chain of transmission that was mentioned.In those honorable hadiths, this is why men’s science appeared, which is the science of wounding and modification.